2018
DOI: 10.2147/jn.s158843
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte-derived macrophages for treatment of cerebral palsy: a study of 57 cases

Abstract: Objective: Cell-based technologies are considered to be a new approach for the treatment of cerebral palsy (CP). Given the potent anti-inflammatory activity and high regenerative potential of M2 macrophages, these cells may be a promising source for cell transplantation. To evaluate the safety and efficacy of autologous M2 macrophages, we performed an open-label, Phase I/ II, non-controlled clinical trial in children with severe CP. Patients and methods: Fifty-seven children with severe CP, including 33 boys a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
4
0
1
Order By: Relevance
“…Injection of the autologous monocyte-derived M2-polarized macrophages at a certain time of gestation (or at the stage of its planning by taking into account the risks of PE) may evolve into a new strategy for PE treatment. Such therapy seems to be promising due to reports about the absence of adverse reactions and long-term side effects after macrophages transplantation in other diseases [120,121]. A possible side effect of the proposed therapy may be the phenomenon of maternal–fetal cellular trafficking—the ability of mother and fetus cells pass the placental barrier [122].…”
Section: Monocyte–macrophage System During Pregnancymentioning
confidence: 99%
“…Injection of the autologous monocyte-derived M2-polarized macrophages at a certain time of gestation (or at the stage of its planning by taking into account the risks of PE) may evolve into a new strategy for PE treatment. Such therapy seems to be promising due to reports about the absence of adverse reactions and long-term side effects after macrophages transplantation in other diseases [120,121]. A possible side effect of the proposed therapy may be the phenomenon of maternal–fetal cellular trafficking—the ability of mother and fetus cells pass the placental barrier [122].…”
Section: Monocyte–macrophage System During Pregnancymentioning
confidence: 99%
“…Macrophage differentiate into two subsets with distinct expression profile, exerting different features and effects on their phenotypes (L. Chen, Sha et al, 2017;Chiu et al, 2016). M1 subset, is normally correlated with overwhelming inflammatory reaction, resulting in the release of proinflammatory cytokines, which potentially have detrimental effects on injured spinal cord (L. Chen, Sha et al, 2017); whereas the activation of M2 subset produces antiinflammatory mediators in injured spinal cord, exhibiting homeostasis, axonal regeneration, and neuroprotection (Chernykh et al, 2018;Chiu et al, 2016). Accordingly, the balance between M1 and M2 microglia subset is considered to play essential roles in pulmonary inflammation (Ying et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, G. biloba extract EGb 761 shifted proinflammatory to anti-inflammatory activation in the AD model of the P301S Tau mutant transgenic mice [54]. This suggested that EGb 761 may be used in the monocytes/macrophages cell-based technologies through the activation of anti-inflammatory cells in vitro because anti-inflammatory M2 macrophages successfully improved neurological functioning of patients with severe cerebral palsy (CP) [85]. The effects of TCM on immunomodulation and neuroinflammation observed in the in vivo study are similarto theeffects of different TCMs demonstrated in vitro, which are summarized in Table 4.…”
Section: Regulation Of Immunomodulation and Neuroinflammationmentioning
confidence: 99%